1995
DOI: 10.1148/radiology.194.3.7862991
|View full text |Cite
|
Sign up to set email alerts
|

Breast cancer diagnosis in women with subglandular silicone gel-filled augmentation implants.

Abstract: Standard mammographic views are inadequate for breast cancer screening in patients with silicone gel-filled implants. Although additional modified compression views offer a moderate improvement in breast cancer detection, imaging with tangential mammographic views, sonography of palpable areas, and breast physical examination in conjunction with mammography will offer additional benefit in breast cancer detection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0
4

Year Published

1996
1996
2012
2012

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(33 citation statements)
references
References 0 publications
0
29
0
4
Order By: Relevance
“…Clinical case series have reported a tendency towards a delayed breast cancer diagnosis among women with breast implants (Gottlieb et al, 1984;Leibman and Kruse, 1990;Silverstein et al, 1990a;Carlson et al, 1993;Fajardo et al, 1995). Overall, epidemiological studies have not been able to confirm such reports.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Clinical case series have reported a tendency towards a delayed breast cancer diagnosis among women with breast implants (Gottlieb et al, 1984;Leibman and Kruse, 1990;Silverstein et al, 1990a;Carlson et al, 1993;Fajardo et al, 1995). Overall, epidemiological studies have not been able to confirm such reports.…”
Section: Discussionmentioning
confidence: 97%
“…However, the issue of potential delay in breast cancer diagnosis in the augmented breast has been raised, since breast implants are radiopaque and this influences the sensitivity of mammography (Eklund et al, 1988;Hayes et al, 1988;Silverstein et al, 1992). Clinical reports have suggested a possible delay and difficulties in the diagnosis of breast cancer (Leibman and Kruse, 1990;Silverstein et al, 1990a;Carlson et al, 1993;Fajardo et al, 1995), but most epidemiological studies have not supported a delay in diagnosis or impaired survival among women with breast implants (Birdsell et al, 1993;Deapen et al, 2000).…”
mentioning
confidence: 99%
“…The Eklund technique is routinely used to aid in visualizing more of the breast tissue [30]. The review by Uematsu discusses the reported sensitivity of the implant displacement technique of 67% compared with standard implant compression of 6% [31]. The CC, MLO, and lateral views can be incorporated to ensure that all of the remaining tissue anterior to the implant is imaged.…”
Section: Implantsmentioning
confidence: 99%
“…2 Silicone implants may obscure mammographic images of the breast tissue and interfere with the interpretation of mammograms, thus hindering detection of breast cancer. [18][19][20] One study estimated that augmentation mammoplasty obscures 22% to 83% of breast tissue on mammography. 21 MRI has been shown to be more sensitive than mammography for identifying coincidental malignancy in women with breast implants.…”
Section: Evaluation Of the Augmented Breastmentioning
confidence: 99%